The Loading Pier, Pitch Lake, Trinidad, B.W.I. - (:unkn) unknown (My University, 2010)
Photograph of the Brighton Pier at La Brea, Trinidad. An aerial tramway loads pitch onto ships waiting by the pier. A number of sheds can also be seen in the photograph. A vehicle is parked in the one on the right.
Colour: Black and White; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Asphalt industry--Trinidad and Tobago; Ships--Trinidad and Tobago; Seashore--Trinidad and Tobago; Aerial tramways--Trinidad and Tobago; Sheds--Trinidad and Tobago; Pitch Lake, The; Brighton Pier (La Brea, Trinidad and Tobago)